The importance of early diagnosis of leprosy in the prevention of disability - Souza, Claudia Fernanda Dias (2010)
Leprosy is well known because it’s neural complications and challenging evolution, despite the established treatment. To avoid the development of physical incapacities, we emphasize the fundamental paper of early diagnose, stopping the appearance of leprosy neuropathies. We describe a case with evolution to ulnar claw.